CODE SWITCHING IN SARAH SECHAN TALK SHOW PROGRAM ON NET TV - Eka Rejeki Maha; Zainuddin Zainuddin; I Wayan Dirgeyasa (Universitas Negeri Medan, 2018)
This study was aimed at examining code switching in Sarah Sechan talk show program on NET TV. The objectives of the study are to find out the types of code switching occurring in the talk show, the process of code switching, and the reasons for code switching in the talk show. This research was conducted by using qualitative descriptive design. The source of data was Sarah Sechan talk show. There were five episodes of Sarah Sechan talk show as the data of this study. The technique of data collection was documentary technique and the instrument of data collection was recorder. The technique of data analysis was interactive model by Miles, Huberman and Saldana (2014). The findings showed that all types of code switching occurred in Sarah Sechan talk show with different proportion. The most dominant type occurring in the talk show is intra sentential switchingThe processes of code switching occurred in Sarah Sechan talk show are insertion, alternation and congruent lexicalization. Reasons for using code switching were expressing solidarity, ethnic identity marker, changing the topic, switching for affective meaning, and emphasizing the meaning. Keywords: Code Switching, Types of Code Switching, Processes of Code Switching, Reasons for Code Switching, Talk Show